HOPES, CHALLENGES, BARRIERS AND ENABLING FACTORS: THE COMPLEXITIES OF BEING AN IMPOVERISHED YOUNG FATHER - Macleod, Catriona (PINS-Psychology in Society, 2025)
Swartz, S & Bhana, A (2009) Teenage tata: Voices of young fathers in South Africa. Cape Town: HSRC Press. ISBN 978-007969-2287-8 pbk; ISBN 978-0-7969-2288-5 pdf download. Pages xiv + 121. In this book, Swartz and Bhana foreground an underexplored topic in the area of adolescent sexual and reproduction health: teen-aged fathers. Given the recent interest by the Departments of Basic Education and Health in teen-aged pregnancies (see reviews by Panday et al [2009], Department Health [2009]), this is a timely book that highlights a number of important issues in relation to young men and fatherhood.